2005
DOI: 10.1111/j.1523-1755.2005.09912.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcium-phosphorous disorders in the progression of renal failure

Abstract: Among factors related to disturbed calcium-phosphate metabolism in chronic kidney disease, the following must be mainly considered as potential culprits in the progression of renal dysfunction: hyperphosphatemia, hyperparathyroidism, lack of active vitamin D, and possibly excess of the phosphaturic hormone FGF 23. Early experimental work suggested a parathyroid hormone (PTH)-independent beneficial role of phosphate restriction on progression in rats (animals with physiologic hyperphosphatemia), so that the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 40 publications
0
18
0
2
Order By: Relevance
“…16 Similarly, in humans, acute rises in serum phosphate on the basis of tumor lysis results in acute kidney injury [17][18][19][20] from renal parenchymal calcification, alterations in renal hemodynamics, and direct tubular cell cytotoxicity. [21][22][23] Multiple case reports and controlled human studies 5-7,24 -26 demonstrated that receipt of a standard regimen of OPS (which contains approximately six times the average daily phosphate intake) results in acute rises in serum phosphate. Moreover, data in rat models of CKD (remnant kidney and nephrotoxic serum nephritis) demonstrate that higher levels of dietary phosphate accelerate loss of kidney function 10,11 and that this effect is attenuated by administration of phosphate binders.…”
Section: Discussionmentioning
confidence: 99%
“…16 Similarly, in humans, acute rises in serum phosphate on the basis of tumor lysis results in acute kidney injury [17][18][19][20] from renal parenchymal calcification, alterations in renal hemodynamics, and direct tubular cell cytotoxicity. [21][22][23] Multiple case reports and controlled human studies 5-7,24 -26 demonstrated that receipt of a standard regimen of OPS (which contains approximately six times the average daily phosphate intake) results in acute rises in serum phosphate. Moreover, data in rat models of CKD (remnant kidney and nephrotoxic serum nephritis) demonstrate that higher levels of dietary phosphate accelerate loss of kidney function 10,11 and that this effect is attenuated by administration of phosphate binders.…”
Section: Discussionmentioning
confidence: 99%
“…Potential culprits for progression are hyperphosphatemia, secondary hyperparathyroidism (sHPT), lack of active vitamin D, and high levels of fibroblast growth factor 23 (FGF23) (3)(4)(5). This hormone is primarily secreted by osteocytes in response to dietary phosphorus overload or increase in 1,25-dihydroxyvitamin D , and it stimulates renal excretion of P, downregulates the production of 1,25-dihydroxyvitamin D, and reduces parathyroid hormone (PTH) levels (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Although in the past it was assumed that vitamin D therapy is "nephrotoxic," probably as a result of vitamin D-induced hypercalcemia in patients with CKD, 7 recent experimental evidence clearly revealed that 1,25-OH 2 D 3 and its analogues attenuate progression in various CKD models. 3,8,9 Finally, the role of FGF23 in CKD progression is unknown.…”
mentioning
confidence: 99%
“…Among factors that are related to calciumphosphate metabolism in patients with CKD, potential culprits for progression are hyperphosphatemia, hyperparathyroidism, lack of active vitamin D, and possibly excess of the recently discovered phosphaturic hormone fibroblast growth factor 23 (FGF23). 3,4 Early experimental work suggested a parathyroid hormone (PTH)-independent beneficial role of phosphate restriction on progres-sion in rats, 5 but it has to be pointed out that these animals have physiologic hyperphosphatemia. Furthermore, there is also little direct experimental or clinical evidence for a role of PTH in accelerating progression, 3 although results from recent experimental studies documented that progression is significantly attenuated by administration of calcimimetics or by parathyroidectomy.…”
mentioning
confidence: 99%
See 1 more Smart Citation